The effect of prolonged time for achieving ovarian suppression before starting stimulation on pregnancy rates in ART cycles - (:unkn) unknown (My University, 2013)
Amaç: Stimulasyona başlamadan önce ovaryen süpresyonun uzamasının gebelik oranlarına etkisini araştırmak Hastalar ve Yöntem: Üniversite affiliye hastanede yardımcı üreme tetkikleri (assisted reproductive technologies (ART)) tedavileri yapılan 565 hasta retrospektif olarak incelendi. Kadınlar gonadotropin salgılayan hormon (gonadotropin releasing hormone (GnRH)) analogu ile ovaryen süpresyon süresine göre gruplandırıldı. GnRH analog kullanım süresine göre grup A alt 25 persentil içinde, grup B de üst 25 persentil içindeki hastalardan oluşmaktaydı. İmplantasyon ve klinik gebelik oranları karşılaştırıldı. Bulgular: Grup Ada ortalama aspire edilen ve insemine edilen oosit sayısı grup Bdekinden fazla idi. İmplantasyon oranları benzer idi. Klinik gebelik oranları benzer idi. Sonuç: Ovaryen süpresyon için geçen zamanın uzaması ART sikluslarında klinik gebelik oranlarını olumsuz etkilemez.

Objective: To determine if the prolonged time for achieving ovarian suppression before starting stimulation affected the pregnancy rates. Patients and Methods: Retrospective cohort analysis was performed on 565 women undergoing first assisted reproductive technologies (ART) treatment in a University-affiliated Hospital. The women were grouped according to the duration of down- regulation by gonadotropin-releasing hormone (GnRH) analogue. Group A consisted of women in the lower 25th percentile, group B consisted of women in the upper 25th percentile, according to the duration of GnRH analogue use. The implantation and clinical pregnancy rates were compared. Results: Mean number of aspirated and inseminated oocytes were more in group A than in group B. Implantation rates were similar. Clinical pregnancy rates were alike. Conclusion: Prolonged time for achieving ovarian supression does not compromise clinical pregnancy rates in ART cycles.
ART sikluslarında stimulasyona başlamadan önce uzamış ovaryen süpresyonun gebelk oiranlarına etkisi
Keywords: Genel ve Dahili Tıp